Agreement between an expert-rated mini job exposure matrix of occupational biomechanical exposures to the lower body and technical measurements or observation: a method comparison study - Andreas Holtermann; Johan Hviid Andersen; Nidhi Gupta; Poul Frost; Susanne Wulff Svendsen; Mette Korshøj; Annett Dalbøge; Peter Fjeldstad Hendriksen (BMJ Open)
Objectives Investigating the agreement between an expert-rated mini job exposure matrix (JEM) of lower body exposures and technical measurements of worktime spent standing/walking and observation-based estimates of time spent kneeling/squatting and total load lifted per workday.Methods We chose 16 job titles from the 121 job groups in the lower body JEM and included them in the mini JEM. New expert ratings for the mini JEM were performed by the same five occupational physicians who performed the ratings for the lower body JEM. For each job title and type of exposure, the exposure estimates were a mean of the five independent ratings. Technical measurements of standing/walking for all 16 job titles, and for 8 job titles workplace observations were performed of kneeling/squatting and total load lifted per workday. Data were collected from September to December 2015 and supplemented by data from the NOMAD and DPhacto studies collected between 2011 and 2013. All data were collected in Denmark. Agreement between expert-based and measured/observed lower body exposures by job titles was evaluated using Spearman’s rank correlation, Bland-Altman plots evaluated systematic deviations and limits of agreement (LoA).Results Standing/walking showed a rank correlation of 0.55, kneeling/squatting 0.83 and total load lifted per workday 0.71. The mini JEM estimates did not systematically deviate from the technical measurements/observations for time spent standing/walking (mean difference 0.20 hours/workday, LoA −1.63, 2.03 hours/workday) and kneeling/squatting (mean difference −0.35 hours/workday, LoA −1.21, 0.51 hours/workday). For total load lifted per workday, the mini JEM systematically overestimated the exposures compared with the observations (mean difference −909 kg/workday, LoA −3000, 1147 kg/workday).Conclusions There was moderate to very high agreement between an expert-rated mini JEM of standing/walking, kneeling/squatting, and lifting exposures and corresponding technical measurements/observations. This method comparison study supports the use of the expert-based lower body JEM in large-scale occupational epidemiological studies.